Un frammento di metafisica descrittiva: i presupposti dell’atteggiamento naturale (Materiali di Estetica. Terza serie, 2023)
The combinatory restriction known in linguistics as selection restrictions are generally assumed to be a kind of linguistic structures, either syntactic or semantic, or at best cognitive structures. The idea discussed in this paper is that selection restrictions, although relevant for the description of complex meanings of linguistic expressions, do not belong to the structure of either language or cognition. Instead, they are criteria for conceptual consistency. They form a layer of shared presuppositions that lie at the grounds of consistent human behaviour and therefore of consistent thought and expression and belong to a natural ontology shared far beyond the boundaries of a given linguistic community.
Keywords: Coherence; Natural ontology; Presuppositions; Ultimate presuppositions; Selection restrictions